Duration of Debt Overhang with Two Lender Banks - Jacek Prokop (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
This paper discusses the duration of the debt overhang with two lender banks. We model the problem as an infinite horizon game with two banks as players. In every period, each bank decides either to sell its loan exposure to the debtor country at the present secondary market price, or to wait and keep its exposure to the next period. Under the assumption of homogeneous price function and short length of periods, we show that the expected duration in the equilibrium becomes large when the degree of homogeneity is low, and tends to 1n 2/ 1n beta^2 (beta is the annual interest factor) as the degree of homogeneity approaches zero. This result implies that the lower bound for the duration is 4 years. We interpret it as a tendency for the debt overhang to last for a somewhat long time.
Keywords: 330